2021
DOI: 10.1111/jdv.17649
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for lymphocytic inflammation in non‐lesional scalp of folliculitis decalvans: an observational study of 25 patients

Abstract: EditorFolliculitis decalvans (FD) is a neutrophilic primary cicatricial alopecia (CA) affecting mostly middle-aged males. Key features include confluent areas of CA, surrounded by polytrichia Figure 1 Folliculitis decalvans. Non-lesional occipital scalp shows inflammatory infiltrate with lymphocytes and histiocytes around the isthmus and vessels. Horizontal section. HE, 200x. Abbreviation: HE, Haematoxylin and eosin staining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Histologically, peri‐ and intrafollicular neutrophils with mixed acute and chronic inflammation with follicular damage are more intense in the upper dermis 2 . As in our case, lymphocytic inflammation around the isthmus with histiocytes and plasma cells can also be seen, which may be indicative of early or subtle stages of FD 3 . On the other hand, classical and evolved FD clinical presentation usually includes tufted hairs, and diffuse dermal scarring may be seen on histology.…”
Section: Figuresupporting
confidence: 58%
“…Histologically, peri‐ and intrafollicular neutrophils with mixed acute and chronic inflammation with follicular damage are more intense in the upper dermis 2 . As in our case, lymphocytic inflammation around the isthmus with histiocytes and plasma cells can also be seen, which may be indicative of early or subtle stages of FD 3 . On the other hand, classical and evolved FD clinical presentation usually includes tufted hairs, and diffuse dermal scarring may be seen on histology.…”
Section: Figuresupporting
confidence: 58%
“…However, clinically in FD, the inflammation is not necessarily restricted in the central scalp and centrifugally expanded. Eyebrows and/or eyelashes, the common predilection sites of KFSD are rarely affected in FD 22 . Through trichoscopy, follicular tufts in KFSD consisted of two to eight hairs in our study, while five to 20 or more are more commonly seen in FD 20 .…”
Section: Discussionmentioning
confidence: 48%
“…Eyebrows and/or eyelashes, the common predilection sites of KFSD are rarely affected in FD. 22 Through trichoscopy, follicular tufts in KFSD consisted of two to eight hairs in our study, while five to 20 or more are more commonly seen in FD. 20 When KFSD evolves into a lymphocyte-dominant infiltrate, the inflammation pattern is similar with LPP.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, another recent non-trichoscopy-guided NAS biopsy study of 25 patients with FD found an association between FD and PIILIF-like features in NAS, including perifollicular infundibula-isthmic lymphocytic inflammation (in 64%) and fibrosis (in 48%). 15 Consequently, PIILIF may be a precursor of both AKN and FD. We also propose that the entities thus far reported as FD-LPP phenotypes 16–18 are likely FD-associated with scalp-wide PIILIF, which in the vicinity of an FD lesion is compounded by the FD-induced alopecia.…”
Section: Discussionmentioning
confidence: 99%